¿Podemos construir la paz? Perspectivas, ritualidades, encuentros - Arango Calad, Carlos; Ortiz, Iván; Quintero Torres, John Alexander; Safatle, Vladimir; Moreno Camacho, Manuel Alejandro; Martínez, Gladys; Vargas, Kelly; Britto Ruiz, Diana; Bustamante Arango, Diana Marcela; Ribot, Jaume Munar; López, Wilson; Rincón Unigarro, Camilo; et al. (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2023)
Can we build peace? relaunches the question of peacebuilding as a commitment to research and reflection beyond established theoretical frameworks. Each chapter of this book reflects the search and the questions that mobilize different scholars from their own intellectual trajectories and life experiences. It is a book that harbors the richness of its content in the diversity of methodical approaches to the question of peace.